Prasarana Ruang Perawatan dengan Tingkat Kepuasan Pasien di RSD Idaman Kota Banjarbaru - Yuliani; Rizany, Ichsan; Setiawan, Herry (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Patient satisfaction is used to evaluate in the Hospital especially as a treatment process. The lack of target patientsatisfaction scores is due to several things, such as treatment room infrastructure. This research is an analyticstudy with cross-sectional design. The sample in this study numbered 134 respondents that used a purposivesampling technique. It used a questionnaire. Analysis test used the Spearman correlation test. The result of thisresearch got an average of a ward facility of 69,87 and an average result of the level patient’s satisfaction of70,97. The result showed that there was a relationship between ward facility with the patient’s satisfaction in theinpatient Idaman Banjabaru Hospital. Ward facility could affect the level of patient’s satisfaction. The result ofthe ward facility shows that it was good while the patient’s satisfaction value was still not reaching the minimumstandard value. There was a relationship ward facility with the patient’s satisfaction in Idaman BanjarbaruHospital.